Fluorescent rotor: Labeling lysosomes, mitochondria and lipid droplets through polarity and viscosity assessment - K.K A.; Maity S.; Pareek N.; Kar P.; Maiti P.; Bhuniya S. (My University, 2025)
The viscosity and polarity of cells are inherent physical parameters, and changes to these attributes are frequently linked to malfunctioning conditions or different diseases. Cancer cells often harbor elevated nonpolar lipid droplets (LDs), acting as energy reserves. The rise in lipid droplets (LDs) and viscosity, distinctive traits of cancer cells, has motivated us to develop a fluorescent probe based on naphthalimide. The fluorescent marker LD-VP exhibits fluorescence signals at 520 nm in nonpolar dioxane and 600 nm in highly viscous glycerol. This implies that probe LD-VP can furnish details regarding cellular microviscosity and lipid droplets within live cells by providing dual-channel images. The probe LD-VP is chemically inert and harmless, enabling its safe utilization in live cell imaging. We conducted fluorescence imaging based on viscosity using probe LD-VP in the red channel, which is found to be co-localized in both mitochondria and lysosomes. Moreover, the probe effectively marks lipid droplets in the green channel. The probe LD-VP represents a distinctive fluorescent tool capable of monitoring both viscosity and lipid droplet expression in live cells. This tool holds the potential for visualizing physiological abnormalities or pathological conditions. © 2024 Elsevier B.V.